Ammonia toxicity affects cations uptake and growth in papaya plants inclusive with silicon addition - Santos Silva, Bruna; de MELLO PRADO, Renato [UNESP]; Calero Hurtado, Alexander [UNESP]; APARECIDA DE ANDRADE, Renata [UNESP]; PEREIRA DA SILVA, Gilmara (Universidad Nacional de Colombia, 2020)
High ammonia (NH4+) concentration can exert stress on many plants, which causes nutritional disorders and reduction on plant growth. However, depending on the intensity of the stress, it may be attenuated by silicon. In this work, the response of impact of cations and silicon accumulations and plant growth in cultivated papaya plants was investigated under different toxic ammonia concentrations regardless of the presence of silicon (Si). The experiment was conducted at the Universidade Estadual Paulista (UNESP) with papaya seedlings, variety ‘Grupo Formosa’ (Calimosa híbrida 01), grown in a glass greenhouse, in 1.7 dm3 pots filled with pine and coconut fiber-based substrate. The experimental design was a randomized block design, in a 5 × 2 factorial arrangement. There were five ammonium concentrations: 10, 20, 40, 80, and 100 mmol L-1 that were delivered via nutrient solution, in the absence and presence of Si (2 mmol L-1), with five replicates. After 31 days of growth, the cations and silicon accumulations in the shoot, plant height, stem diameter, root, and shoot dry matter were evaluated. Results revealed that increased ammonia concentration showed toxicity in papaya plants and stronger reductions in Ca, Mg, K and Si accumulations, plant heights, stem diameters, and root and shoot dry matter production, even when silicon was present and with greater effects on the shoot dry matter (87 %) than that of the roots (13 %).
Toxicidad amoniacal afecta la absorción de cationes y el crecimiento de plantas de papaya inclusive con adición de silicio
Keywords: Biomass; Carica papaya; Nitrogen; Nutrients; Phytotoxicity